The potential impact of the neurosciences on religious and spiritual education: ramifying from the impact on values education - Mudge, Peter (Journal of beliefs and values, 2014)
This article will argue that neuroscientific insights can inform religious and spiritual education’s capacity for strengthening student understanding, promoting transformation and ultimately wisdom. Among other findings, it will show that current neuroscientific research supports a holistic approach to pedagogy which emphasises the cognitive, affective, moral and other dimensions of student learning and the corresponding need to facilitate development in all of these dimensions in order for authentic learning to take place. As such, the article adopts a cross-disciplinary reference point, referring to research that has demonstrated the usefulness of neuroscientific findings in application to education through a specific focus on values education. Values education is held up as a discipline with complementary interests to a holistic religious and spiritual education, these interests being in its capacity to inculcate in students the character dispositions which orientate them towards moral excellence, so allowing them to navigate complex ethical terrain, contribute constructively to society, and ultimately achieve human flourishing (Porter 2001; Becker 2004; Narvaez 2007; Rachels 2007). Drawing on what has been demonstrated above, we will argue that neuroscientific insights can help in understanding and facilitating religious and spiritual education as holistic and able to respond to contemporary issues of personal identity and social friction and, furthermore, as uniquely poised to contribute to contemporary educational research, including around the intersections between neuroscience and education.